A case of incidental pulmonary benign metastasizing leiomyoma - Aydın, Suphi; Öz, Gürhan; Dumanlı, Ahmet; Gencer, Adem; Balcı, Aydın; Demirağ, Funda (Journal of Surgery and Medicine, 2021)
Benign metastasizing leiomyoma is exceedingly rare. Pulmonary benign metastasizing leiomyoma is defined as the metastasis of leiomyoma to the lung tissue. It has a benign histological character, but the presence of metastasis is contradictory. First reported in 1937, it is generally seen among women of young reproductive age and premenopausal women who have undergone uterine leiomyoma or hysterectomy, and the most common site of metastasis is the lung. The prognosis is generally very favorable, and it rarely undergoes a malignant transformation. However, various studies suggest that pulmonary and pleural leiomyoma may cause acute respiratory failure. Radiological findings have a wide spectrum ranging from primary malignant neoplasms to metastatic diseases. Benign metastasizing leiomyoma is usually incidentally found on chest x-rays, and it appears as nodules arising from the benign proliferation of smooth muscles. Here, we present a 46-year-old patient who had a hysterectomy 15 years ago due to uterine leiomyoma and was recently diagnosed with benign leiomyoma which metastasized to the lung. It should be kept in mind that benign leiomyomas with pulmonary metastasis may rarely undergo malignant transformation.